Integral de (x^2)*e^(-ax) dx
Solución
Respuesta (Indefinida)
[src]
/// 2 2 \ -a*x \
||\-2 - a *x - 2*a*x/*e 3 |
/ ||-------------------------- for a != 0|
| || 3 |
| 2 -a*x || a |
| x *E dx = C + |< |
| || 3 |
/ || x |
|| -- otherwise |
|| 3 |
\\ /
∫e−axx2dx=C+{a3(−a2x2−2ax−2)e−ax3x3fora3=0otherwise
/ / 2 \ -a
|2 \-2 - a - 2*a/*e
|-- + ------------------- for And(a > -oo, a < oo, a != 0)
< 3 3
|a a
|
\ 1/3 otherwise
{a3(−a2−2a−2)e−a+a3231fora>−∞∧a<∞∧a=0otherwise
=
/ / 2 \ -a
|2 \-2 - a - 2*a/*e
|-- + ------------------- for And(a > -oo, a < oo, a != 0)
< 3 3
|a a
|
\ 1/3 otherwise
{a3(−a2−2a−2)e−a+a3231fora>−∞∧a<∞∧a=0otherwise
Piecewise((2/a^3 + (-2 - a^2 - 2*a)*exp(-a)/a^3, (a > -oo)∧(a < oo)∧(Ne(a, 0))), (1/3, True))
Estos ejemplos se pueden aplicar para introducción de los límites de integración inferior y superior.